The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1516-89132005000400029
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological evaluation of rejects from the wood industry

Abstract: This study aimed chemical characterization and microbiological evaluation of extracts obtained from the waste of woods marketed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Mitidiero (2002) demonstrou que esta terapia alternativa permite manter a sanidade do rebanho em padrões semelhantes aos da alopatia, constituindo-se assim, em uma opção viável para os produtores de leite. Estudos in vitro visando à determinação do potencial antimicrobiano de plantas pertencentes à flora brasileira têm demonstrando resultados satisfatórios (Granato et al 2005, Oliveira et al 2007, Ushimaru et al 2007), porém observase a descontinuidade destes estudos e uma fragmentação dos resultados, não permitindo muitos avanços na área.…”
Section: Estratégias De Controle E Prevençãounclassified
“…Mitidiero (2002) demonstrou que esta terapia alternativa permite manter a sanidade do rebanho em padrões semelhantes aos da alopatia, constituindo-se assim, em uma opção viável para os produtores de leite. Estudos in vitro visando à determinação do potencial antimicrobiano de plantas pertencentes à flora brasileira têm demonstrando resultados satisfatórios (Granato et al 2005, Oliveira et al 2007, Ushimaru et al 2007), porém observase a descontinuidade destes estudos e uma fragmentação dos resultados, não permitindo muitos avanços na área.…”
Section: Estratégias De Controle E Prevençãounclassified
“…Aspidosperma polyneuron Müll. Arg., a related species that is commonly known as "peroba-rosa", is a tree that is locally used as astringent, antipyretic, antidiarrheal and especially as anti-malarial agent (Botsaris, 2007), and studies have proven the antimicrobial effect of its leaves, stems and roots (Ferreira et al, 2003;Granato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studying tailings from the processing of hardwoods in Paraná (Brazil), it was found that the methanol extract of the wood of the plant identified as Peroba pink (Aspidosperma sp.) had a composition rich in phenols and alkaloids as well as strong activity against gram-negative bacteria Proteus mirabilis [105]. In two trials conducted with various plant species, among them five from Aspidosperma genre, it was observed that the ethanol extract of the stem bark of A. excelsum, A. megalocarpon, A. oblongum and A. marcgravianum were active against gram-positive bacteria Bacillus subtilis and that the same extracts and also the ethanol extract of the stem bark of A. album were active against gram-positive S. aureus [106,107].…”
Section: Phytochemicals -Isolation Characterisation and Role In Humamentioning
confidence: 99%